Modelling and optimization of free fatty acid reduction in bulk palm cooking oil. Issue 1 (November 2021) - Kristianingsih, W; Liana, V; Rohmatulloh, B; Prakoso, I; Fauzy, M R; Argo, B D; Hendrawan, Y
Abstract: Bulk cooking oil from palm oil processing is one of the biodiesel materials which is available in large quantities. The pre-treatment process can be done by adding 100 mesh activated zeolite adsorbent as a substitute for the esterification process to reduce free fatty acid (FFA). The purpose of this research was to model and optimize the zeolite concentration and adsorption time to reduce free fatty acids in bulk palm cooking oil. This study used a response surface method with a central composite design (CCD), resulting in 13 experimental combinations of two factorial treatments, i.e. the concentration of zeolite adsorbent and adsorption time. The zeolite concentration and the adsorption time with an upper limit of 30% and 120 minutes and a lower limit of 10% and 60 minutes had a significant effect on the FFA reduction. The best model was a quadratic model. The testing of validation data used the recommended optimum combination, i.e. the zeolite concentration of 10.59% and the adsorption time of 101.57 minutes resulting in a deviation of 5.37% between the predicted data and the actual data.